Low absorption of silicon via foliar in comparison to root application has an immediate antioxidant effect in mitigating water deficit damage in sugarcane - Teixeira, Gelza Carliane Marques [UNESP]; de Mello Prado, Renato [UNESP]; Rocha, Antonio Márcio Souza [UNESP] (Wiley, 2021)
High root absorption of silicon (Si) in sugarcane plants that accumulate the element attenuates water deficit-induced damage. However, there is a lack of research to identify whether the low relative absorption of Si via leaf spraying compared to root application has an immediate antioxidant effect on plants under water restriction. For this purpose, the objective of this research was to evaluate the effect of Si applied via leaf spraying and via nutritive solution (root) in mitigating the damage caused by short-term water deficit induced by PEG-6000 in pre-sprouted sugarcane seedlings. The treatments were arranged in a 3 × 2 factorial scheme, consisting of the forms of Si supply: via nutrient solution (SiR) (2.0 mmol/L), via foliar spraying (SiL) (3.4 mmol/L) plus the absence of Si (−Si), combined with the presence (−0.6 MPa) and absence of water deficit, arranged in randomized blocks with 6 repetitions. The experiment was developed in a hydroponic system, in which Si was initially supplied during the seedling production phase; subsequently, water deficit was induced with PEG-6000 for a period of 72 hr. Plants under water deficit increased the accumulation of Si with the supply of the element via root application and via foliar spraying by 2118% and 98%, respectively, in comparison to the absence of Si. However, although Si foliar absorption was relatively low in comparison to the root, the physiological effects in relieving water deficit-induced stress were equal to or even higher than those of root application. In conclusion, the amount of Si absorbed by the plant is not a major factor to induce an antioxidant defence response to mitigate the immediate effects of water deficit, since the two forms of application of Si were similar. Si foliar spraying promotes physiological and biochemical effects that alleviate damage done water deficit short term, even on plants with an active absorption mechanism such as sugarcane.
Keywords: abiotic stress; beneficial element; plant nutrition